A Future for Flint Hills Barns - Christy Davis (Symphony in the Flint Hills, 2016)
Considering the way they are romanticized in countless books, photographs, and paintings, it might seem that there is an inexhaustible number of Kansas barns.
Keywords: barns; hay storage; ranches; farms; Flint Hills; landscape; prairie; native; grasses; national; Kansas Barn Alliance; ONE SWIFT RAIN; Katie Twiss; MOVING TO FORGOTTEN; Jody Lightner; COUNTRY CLAIM; Justin Marable; COLOR IN THE BLUESTEM; Chris Wolf Edmonds